An Analysis Of Slang Words Meaning In Memes On The Pinterest Platform: A Study Of Semantic - Meiske Lovian Sinaga; Nurhayati Sitorus; Sahlan Tampubolon (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This research aimed to analysis the semantic meanings of slang words found in phemes on the Pinterest platform. The study employed a qualitative descriptive approach and applied semantic theory to examine and explain the meanings of slang expressions. The data were slang words taken from memes on Pinterest, which were collected through observation, documentation, and field notes. The data were then analysis using Miles and Huberman's interactive model, which consisted of data condensation, data display, and drawing conclusions. The findings revealed that the slang words identified in Pinterest memes could be classified into three types of semantic namely, Denotation and Sense, Lexical and Structural Meaning, and Categorematic and Syncategorematic Expressions. This reflects the nature of memes as short, creative, and meaningful communication in digital culture. This study contributes to the understanding of how slang operates semantically in digital communication and provides insights into the role of language creativity in online popular culture. The discussion that slang in Pinterest memes does not merely function as informal vocabulary but as a form of linguistic creativity that blends literal and figurative meaning with visual context. Compared with previous studies focusing on Instagram, TikTok, or advertisements, this research shows that Pinterest memes demonstrate more layered semantic interpretations, as the combination of text and images enriches meaning. Thus, the study confirms the relevance of semantic theory in analyzing online discourse and contributes to understanding how digital communities construct and interpret meaning through slang.